2023
DOI: 10.1038/s41598-023-43650-5
|View full text |Cite|
|
Sign up to set email alerts
|

Keystone seabird may face thermoregulatory challenges in a warming Arctic

Melissa L. Grunst,
Andrea S. Grunst,
David Grémillet
et al.

Abstract: Climate change affects the Arctic more than any other region, resulting in evolving weather, vanishing sea ice and altered biochemical cycling, which may increase biotic exposure to chemical pollution. We tested thermoregulatory impacts of these changes on the most abundant Arctic seabird, the little auk (Alle alle). This small diving species uses sea ice-habitats for foraging on zooplankton and resting. We equipped eight little auks with 3D accelerometers to monitor behavior, and ingested temperature recorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…During the remaining time, birds engage in energetically demanding activities such as flying and diving (flying: 7.24 × basal metabolic rate; diving: 9.37 × basal metabolic rate [36]), which may lead to overheating. Yet, recent field measurements [37] demonstrated that dovekies efficiently alternate periods spent flying and diving, with resting at sea or at the colony enabling the rapid dissipation of muscular heat and body temperature decline.…”
Section: Resultsmentioning
confidence: 99%
“…During the remaining time, birds engage in energetically demanding activities such as flying and diving (flying: 7.24 × basal metabolic rate; diving: 9.37 × basal metabolic rate [36]), which may lead to overheating. Yet, recent field measurements [37] demonstrated that dovekies efficiently alternate periods spent flying and diving, with resting at sea or at the colony enabling the rapid dissipation of muscular heat and body temperature decline.…”
Section: Resultsmentioning
confidence: 99%